Analysis of the optical properties of ZnO thin films deposited on a glass substrate by the So-gel method - Wilda Amananti; Riky Ardiyanto; Heri Sutanto; Iis Nurhasanah; Inur Tivani (Journal of Natural Sciences and Mathematics Research, 2022)
Zinc oxide (ZnO) has attracted the attention of researchers as a photocatalyst material, because ZnO has a wide direct band gap (3.37 eV) and is a semiconductor material with a large excitation binding energy (60 meV). ZnO is a photocatalyst that has many advantages, namely cheap, non-toxic, and theoretically very active under UV irradiation. The most interesting thing about ZnO semiconductor compared to other semiconductors is that ZnO can absorb most of the solar spectrum. However, there is a weakness of the ZnO semiconductor, namely the very fast recombination of charge carriers and the ZnO semiconductor has a low efficiency in the visible region which causes the ZnO semiconductor to have a wide band gap. that is the weakness of ZnO. it is necessary to choose the right method to overcome this deficiency of ZnO. one way that can be done is to increase the photocatalytic ability of zinc oxide, it is necessary to develop it in the manufacture of thin films. The method used in the manufacture of Thin Film is using the sol-gel spray coating method. the first stage is through the manufacture of ZnO precursors by dissolving zinc acetate dehydrate with isopropanol solvent through stirring. then the second stage by adding Monoethanolamine. This stirring lasted for 30 minutes at a temperature of 70°C, the precursor concentration was prepared with three different concentrations which included concentrations of 0.1, 0.3, and 0.5 M. ZnO precursor deposited on the substrate glass is blown at 400 °C. Optical properties are carried out by recording the transmittance and absorbance which are affected by increasing concentrations. The optical transmission spectra show that the transmission increases with decreasing concentration and the maximum transmission in the visible region is about 90% for ZnO thin films prepared with 0.1 M. The optical band gap value produced by the thin film of 0.1 M precursor concentration resulted in an energy band gap of 3.11 eV; thin films of 0.3 M precursor concentration produced an energy band gap of 3.07 eV; and thin film of 0.5M precursor concentration produced an energy band gap of 3.06 eV.©2022 JNSMR UIN Walisongo. All rights reserved.